Edutourism Initiative in Pulau Santen Beach, Banyuwangi Through Local Community Empowerment by Sea Turtle Conservation Program - Yudhana, Aditya; Firmansyah, Januar; Praja, Ratih Novita; Yulianti, Yunika Tri; Sari, Jayanti Dian Eka; Mandagi, Ayik Mirayanti; Haditanojo , Wiyanto; Hamonangan, Jonathan Mark (Journal of Basic Medical Veterinary, 2023)
The potential of Santen Island beach, which has been known as a tourist beach, is increasingly visible with the amount of infrastructure and tourism built by the local government. This is done as an effort to promote Santen Island, as one of the best natural tourism centers in Banyuwangi. The people of Santen Island must be prepared as a group that is aware of the potential of their village and the sustainability of its natural tourism. Santen Island is also a tourist location that is annually used as a nesting site for sea turtles that land on the coast of Banyuwangi. This is actually very contrary to the natural habits of sea turtles which prefer to make nests in quiet places without the disturbance of sound, light, and humans. Because this natural nesting site is a tourist attraction, the local residents should also be given insights related to the protection of sea turtles that land on the coast of Santen Island as wildlife protected by the Conservation Law in Indonesia. This community service aims to strengthen the awareness and knowledge of the Santen Island tourism awareness group related to the importance of the role of the community around the beach to participate in preserving wildlife and their ecosystems. The methods used to carry out community service are lectures, discussions, and brainstorming. The location of the implementation is on the beach of Pulau Santen with the target group of people in the Pulan Santen beach area. The locality development model is applied in community service activities. The understanding, awareness, and participation of the target group increased. Through the community service activities that have been carried out, the sustainability of the program is needed until a conservation education tourism model is formed that has the potential to improve the economy of the surrounding community and the preservation of biodiversity in the region. This activity provides an increase in knowledge, awareness, and participation of the target group in managing the conservation of wildlife and their ecosystems, especially sea turtles.